1991
DOI: 10.1210/endo-128-6-2976
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin Receptor Gene Expression in Rat Mammary Gland and Liver during Pregnancy and Lactation

Abstract: The expression of two forms of PRL receptor messenger RNA was measured at different stages of pregnancy and lactation in mammary gland and liver from Sprague-Dawley rats, using 32P-labeled complementary DNA probes encoding the extracellular part of the receptor (E probe), common to the two forms and a probe encoding the intracellular part of the long form of the receptor (I probe), that only recognizes sequences specific to the long form of the receptor. Hybridizations were performed in Northern blots obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
2
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(73 citation statements)
references
References 35 publications
4
66
2
1
Order By: Relevance
“…For instance in rats, prolactin concentration in plasma increases significantly just before parturition and remains high for the entire lactation [110], accompanied also by a concomitant increase in prolactin receptor [111] which appears similar to the pattern of prolactin receptor in mouse mammary during lactation [112]. In contrast, prolactin concentration in dairy cows increases dramatically at the onset of lactation and decreases afterwards to levels observed prior parturition, and prolactin receptor expression does not increase [4].…”
Section: Regulation Of Milk Protein Expressionmentioning
confidence: 73%
“…For instance in rats, prolactin concentration in plasma increases significantly just before parturition and remains high for the entire lactation [110], accompanied also by a concomitant increase in prolactin receptor [111] which appears similar to the pattern of prolactin receptor in mouse mammary during lactation [112]. In contrast, prolactin concentration in dairy cows increases dramatically at the onset of lactation and decreases afterwards to levels observed prior parturition, and prolactin receptor expression does not increase [4].…”
Section: Regulation Of Milk Protein Expressionmentioning
confidence: 73%
“…Both GHR (Mertani et al, 1998) and PRLR (Jahn et al, 1991) are expressed in the mammary gland. The respective activity of GH on the GHR and the PRLR diers related to what species the GH is derived from.…”
Section: Receptor Specificitymentioning
confidence: 99%
“…It has been reported that PRL-RL mRNA is dominant in the mammary glands of lactating mice [27], rabbits [28] and rats [29], but the dominant PRL-R mRNA species is for PRL-Rs mRNA in the mouse [19] and rat liver [30]. Although three PRL-Rs mRNA species are reported in the mouse ovary [23], 5'-and 3'-primers used here are able to anneal with these PRL-Rs cDNAs and to be used for amplification in PCR.…”
Section: Discussionmentioning
confidence: 99%